Using MCPs (Model Context Protocol) to eliminate 50% of tickets in Information Technology Services - Raman Krishnaswami (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The current paper investigates the implementation of Model Context Protocols (MCPs) in mitigating support tickets in Information Technology (IT) services. With the help of MCPs, context is better understood, and repetitive work processes are automated, requiring less time for resolution. The number of support team tickets is also found to be reduced by 50 percent after the application of MCPs, according to recent data recorded in various service centers. It was further observed that the accuracy and speed of response increase. MCPs prove useful in enabling service teams to perform more efficiently and hasten service delivery to customers. The study explains how MCPs combine automation and intelligence to facilitate improved service delivery and cost reduction in IT support departments.